1995
DOI: 10.1111/j.1540-6261.1995.tb04042.x
|View full text |Cite
|
Sign up to set email alerts
|

Managers of Financially Distressed Firms: Villains or Scapegoats?

Abstract: In this article, we provide evidence concerning the extent to which managers are to blame when their firms become bankrupt. We study a sample of firms that file for Chapter 11 and determine the actions taken by the firms' managers during the three‐year period before the filing. We compare the sample with a control sample of firms that performed better. We suggest that the comparison provides evidence on the way managers act as their firms sink into financial trouble and whether financial distress is the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(53 citation statements)
references
References 40 publications
4
46
1
2
Order By: Relevance
“…However, proponents of scapegoating theory report that little meaningful change occurs after succession (Sakano and Lewin, 1999). Scapegoating theory suggests that, in underachieving organizations, blame for poor performance is placed on a top manager for being responsible for strategy or its execution (Khanna and Poulsen, 1995). However, Khanna and Poulsen (1995) found that such managers are scapegoats for greater endemic problems, finding no evidence that past managerial decisions are the root causes of organizational failings.…”
Section: Short-term Performance After Manager Changementioning
confidence: 99%
See 2 more Smart Citations
“…However, proponents of scapegoating theory report that little meaningful change occurs after succession (Sakano and Lewin, 1999). Scapegoating theory suggests that, in underachieving organizations, blame for poor performance is placed on a top manager for being responsible for strategy or its execution (Khanna and Poulsen, 1995). However, Khanna and Poulsen (1995) found that such managers are scapegoats for greater endemic problems, finding no evidence that past managerial decisions are the root causes of organizational failings.…”
Section: Short-term Performance After Manager Changementioning
confidence: 99%
“…Scapegoating theory suggests that, in underachieving organizations, blame for poor performance is placed on a top manager for being responsible for strategy or its execution (Khanna and Poulsen, 1995). However, Khanna and Poulsen (1995) found that such managers are scapegoats for greater endemic problems, finding no evidence that past managerial decisions are the root causes of organizational failings. Consequently, change gives rise to disruption which masks underlying problems, thereby causing further damage to performance in the short term (Brown, 1982), as is indicative of vicious circle theory.…”
Section: Short-term Performance After Manager Changementioning
confidence: 99%
See 1 more Smart Citation
“…Second, corporate boards may replace managers of poorly performing firms even if the managers are not responsible for the poor performance. (See, for example, Khanna and Poulsen (1994).) Under neither of these scenarios would a change in management necessarily be expected to generate performance improvements.…”
Section: Internal Monitoring Mechanisms Have Recently Received Considmentioning
confidence: 99%
“…However, the stock market's reaction to top-management changes in distressed firms is mixed. Announcements of change in senior management in distressed firms are greeted positively (Bonnier and Bruner, 1989), negatively (Khanna and Poulsen, 1995) or neutrally (Warner, Watts and Wruck, 1988;Weisbach, 1988) by the market.…”
Section: Managerial Restructuringmentioning
confidence: 99%